2020
DOI: 10.3390/ijms21041300
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Effect of Inorganic and Organic Chemicals with Silver Nanoparticles on Soybean under Flooding Stress

Abstract: Extensive utilization of silver nanoparticles (NPs) in agricultural products results in their interaction with other chemicals in the environment. To study the combined effects of silver NPs with nicotinic acid and potassium nitrate (KNO3), a gel-free/label-free proteomic technique was used. Root length/weight and hypocotyl length/weight of soybean were enhanced by silver NPs mixed with nicotinic acid and KNO3. Out of a total 6340 identified proteins, 351 proteins were significantly changed, out of which 247 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 75 publications
0
21
0
3
Order By: Relevance
“…It was shown that calcium ion in the root tip and cotyledon was induced by flooding, and calcium-related proteins such as calreticulin and pyruvate decarboxylase, which were associated with protein folding and pyruvate catabolism, responded to flooding [ 40 , 41 , 42 , 43 ]. The deleterious effect of flooding was evident with cell death, which occurred in 2-day-old soybean exposed to flooding for 1 day and as long as 6 days [ 17 , 44 , 45 ]. Elucidation of cellular metabolism showed that protein metabolism [ 16 , 38 , 42 , 46 , 47 ], RNA metabolism [ 38 , 48 ], energy management [ 44 , 49 ], carbohydrate metabolism [ 50 , 51 ], and carbon-nitrogen flux [ 51 , 52 , 53 ] responded to flooding.…”
Section: Morphological and Physiological Effect Of Flooding Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…It was shown that calcium ion in the root tip and cotyledon was induced by flooding, and calcium-related proteins such as calreticulin and pyruvate decarboxylase, which were associated with protein folding and pyruvate catabolism, responded to flooding [ 40 , 41 , 42 , 43 ]. The deleterious effect of flooding was evident with cell death, which occurred in 2-day-old soybean exposed to flooding for 1 day and as long as 6 days [ 17 , 44 , 45 ]. Elucidation of cellular metabolism showed that protein metabolism [ 16 , 38 , 42 , 46 , 47 ], RNA metabolism [ 38 , 48 ], energy management [ 44 , 49 ], carbohydrate metabolism [ 50 , 51 ], and carbon-nitrogen flux [ 51 , 52 , 53 ] responded to flooding.…”
Section: Morphological and Physiological Effect Of Flooding Stressmentioning
confidence: 99%
“…With regard to flooding-mediated energy metabolism, Al 2 O 3 -NPs with sizes of 30–60 nm played positive roles; however, particles of 5 and 135 nm posed negative effects, indicating that Al 2 O 3 -NPs with various sizes affected the membrane permeability of mitochondria and the activity of the TCA cycle [ 99 ]. In addition, soybean treated with a mixture of Ag-NPs, nicotinic acid, and KNO 3 displayed better growth than that treated with Ag-NPs alone, which was through regulation of activated protein quality control for misfolded proteins [ 45 ]. Collectively, these results indicate that NP treatment promotes soybean survival from flooding mainly through maintaining mitochondria function, which could alleviate the energy shortage and lipid oxidation induced by flooding stress.…”
Section: Proteomic Analysis To Understand Flood-tolerant Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteomic techniques are used in the identification of stress-responsive mechanism in plants under conditions such as salt [ 14 ], cold [ 19 ], flood [ 20 ], and wounding [ 21 ]. Wang et al [ 19 ] provided insights into the cold stress responses of early imbibed castor seeds: proteins confer cold tolerance by promoting protein synthesis, protect the cell against damage caused by cold stress, and facilitate resistance or adaptation to cold stress by the increased content of unsaturated fatty acid.…”
mentioning
confidence: 99%